Evolution of the coloration of glass frogs (Anura: Centrolenidae) and its relationship with altitudinal gradients in the Neotropic María José Sánchez Carvajal Napo - Ecuador 2022 - Carvajal Sánchez, María José (2022)
The Andes played an important role in the flora and fauna evolution of South America. The Andes played an important role in flora and fauna evolution of South America. The Centrolenidae family comprises more than 156 species with high diversity and endemism in the Andes. Herein, we investigate the biogeographic history of this family using molecular phylogenetics and dating, to determine the role of the Andean uplift in the diversification of dorsal color patterns of species in the Neotropical region. For phylogenetic reconstruction, we used data on the coloration patterns of 120 glass frog species and sequences of nuclear genes (c-myc, POMC, and RAG-1) and mitochondrial genes (12S, 16S, and ND1). In addition, information on elevational distributions was used for biogeographical reconstruction across ancestral areas among lineages. We found that the rise of the Northern Andes is strongly associated with lineage diversification processes during the last 10 million years, promoting the evolution of color patterns in the altitudinal gradient. Biogeographically, highlands harbor the greatest number of chromatic characteristics, both in life and in preservation. Our study demonstrates the importance of mountain orogeny as driver of rapid lineage diversification and color evolution patterns in the family Centrolenidae in the Neotropics